Dissecting the Phenotype and Genotype of PLA2G6‐Related Parkinsonism. Issue 1 (8th October 2021) - Magrinelli, Francesca; Mehta, Sahil; Di Lazzaro, Giulia; Latorre, Anna; Edwards, Mark J.; Balint, Bettina; Basu, Purba; Kobylecki, Christopher; Groppa, Sergiu; Hegde, Anaita; Mulroy, Eoin; Estevez‐Fraga, Carlos; et al.
ABSTRACT: Background: Complex parkinsonism is the commonest phenotype in late‐onset PLA2G6 ‐associated neurodegeneration. Objectives: The aim of this study was to deeply characterize phenogenotypically PLA2G6 ‐related parkinsonism in the largest cohort ever reported. Methods: We report 14 new cases of PLA2G6 ‐related parkinsonism and perform a systematic literature review. Results: PLA2G6 ‐related parkinsonism shows a fairly distinct phenotype based on 86 cases from 68 pedigrees. Young onset (median age, 23.0 years) with parkinsonism/dystonia, gait/balance, and/or psychiatric/cognitive symptoms were common presenting features. Dystonia occurred in 69.4%, pyramidal signs in 77.2%, myoclonus in 65.2%, and cerebellar signs in 44.6% of cases. Early bladder overactivity was present in 71.9% of cases. Cognitive impairment affected 76.1% of cases and psychiatric features 87.1%, the latter being an isolated presenting feature in 20.1%. Parkinsonism was levodopa responsive but complicated by early, often severe dyskinesias. Five patients benefited from deep brain stimulation. Brain magnetic resonance imaging findings included cerebral (49.3%) and/or cerebellar (43.2%) atrophy, but mineralization was evident in only 28.1%. Presynaptic dopaminergic terminal imaging was abnormal in all where performed. Fifty‐four PLA2G6 mutations have hitherto been associated with parkinsonism, including four new variants reported in this article. These are mainly nontruncating, which may explain the phenotypic heterogeneity of childhood‐ and late‐onset PLA2G6 ‐associated neurodegeneration. In five deceased patients, median disease duration was 13.0 years. Brain pathology in three cases showed mixed Lewy and tau pathology. Conclusions: Biallelic PLA2G6 mutations cause early‐onset parkinsonism associated with dystonia, pyramidal and cerebellar signs, myoclonus, and cognitive impairment. Early psychiatric manifestations and bladder overactivity are common. Cerebro/cerebellar atrophy are frequent magnetic resonance imaging features, whereas brain iron deposition is not. Early, severe dyskinesias are a tell‐tale sign. © 2021 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society